량치차오, 루쉰, 장타이옌의 미래 상상 - 현실인식과 정치성을 중심으로 - 송인재; Song Injae (중국연구, 2017)
At the beginning of the twentieth century, the Chinese intellectuals gained insight into reality and formed critical opinions through self-help, political activities, and intellectual work. In addition, Liang Qi chao, Lu xun, Zhang Taiyan actively portrayed a Utopia that overcame the reality of the time. He introduced his own position as a constituency through the genre of political novels and future novels, naming his vision as 'New China Future'. Lu Xun focused on the inner of human beings. In order to solve the inner problem, I claimed 'Inner Light' and 'Sound of Mind', and defined the state in which everyone 's personality was expressed as 'Cultivating Personality'(立人). He also called the nation constructed by them as ‘Nation of People’(人國). Zhang Taiyan, interpreting Qiwulun(齊物論) presented epistemological question. He also derives the theory of equality through interpretation, criticizing the discourse of civilization and criticizing the Western imperialism behind it. At the beginning of the 20th century, China faced a problematic and pessimistic situation of decline and crisis. Paradoxically, however, in the pessimistic reality, thoughts and desires for a better world have been created and developed intensely.